Co2+, Fe2+, and Ni2+: Modifiers for Photocatalytic Deposition of Highly Active Pt on Graphene-Based Supports - Haghmoradi, Navid; Sari, Zahide Tugba; Kirlioglu, Ahmet Can; Kaplan, Begum Yarar; Dedeoglu, Burcu; Zahedimaram, Pegah; Abdolhosseinzadeh, Sina (Amer Chemical Soc, 2022)
This study focuses on photocatalytic syntheses, in which transition metal ions (Co2+, Fe2+, or Ni2+), as the hole scavengers and surface modifiers of partially reduced graphene oxide, PRGO, were utilized to photoreduce Pt4+. A pulsed UV reactor was used to illuminate the precursors. The electrostatic interaction between the metal ions (Co2+, Fe2+, or Ni2+) and the oxygen functional groups on PRGO was the main parameter, proposed to be the reason controlling Pt4+ reduction and Pt structure and activity. The alternative assumption in managing the oxidation states of Pt was the variation in the oxidation rates of hole scavengers. Pt electrocatalysts' structural and electrochemical characteristics revealed that utilizing the cobalt-based hole scavenger caused a dominant growth phase of Pt particles at preferred positions on PRGO, with metallic states and improved electrocatalytic activities (ECSA value of 191 m2 center dot g-1 for Co2+ vs 141 m2 center dot g-1 and 127 m2 center dot g-1 for Fe2+ and Ni2+, respectively). Density functional theory (DFT) calculation, on the other hand, suggested that the greater affinity of cobalt and iron ions to oxygen groups could detach more O from the graphene plane. Based on the DFT results, less O groups in the vicinity of Pt particles gave an amorphous morphology to Pt and facilitated the hydrogen oxidation reaction (HOR).
Keywords: Hole scavenger; Photocatalytic deposition; Transition metal; Graphene; Electrocatalyst; PEM fuel cell